IMPLEMENTASI KELAS GLOKALISASI DALAM PEMBELAJARAN SASTRA: PERSPEKTIF MAHASISWA DALAM MENGANALISIS KARYA SASTRA LOKAL DAN GLOKAL - Linaria Arofatul Ilmi Uswatun Khasanah; Wahono Widodo; Neni Mariana; Heru Subrata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to explore the application of glocalization classes in literature learning, focusing on the analysis of local and glocal literary works by university students. In the context of globalization, glocalization classes integrate literary works from local and global cultures, providing a broader perspective in understanding universal values. This study used a qualitative research method with a case study design, involving students of the S1 Elementary School Teacher Education Study Program at Muhammadiyah Lamongan University. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman analysis model. The results showed that students could identify similarities and differences between Timun Mas and Hansel and Gretel literary works, as well as understand the values of courage, ingenuity, and struggle against injustice in both stories. Glocalization learning helps students connect these values to their cultural context and encourages the application of positive values in daily life. This study concludes that glocalization classes are effective in enriching students' understanding of literature and values relevant to life challenges.